Pengaruh Getok Tular Elektronik Pada Citra Merek dan Minat Beli Konsumen Produk Telepon Cerdas - , AVECINNA C A; , Bayu Sutikno, M.S.M., ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The development of information technology in the era of globalization is now making it easier for consumers to search for information about a product, and eventually will be able to influence the purchase decisions of consumers. Internet is one of the platform that can be used for searching information on products (e-WOM). The purpose of the study is to determine the extent to which electronic word of mouth among consumers can influence brand image and purchase intention. This study uses data which obtained by distributing questionnaires to 151 respondents. Analysis tools used in this study are simple regression and multiple regression. The results of the study show that all the hypotheses are supported. The conclusion that can be drawn from these results is that the electronic word of mouth positively affect brand image and purchase intention, and brand image also positively affect purchase intention.